Relationship between heart rate and water depth during standing in water - Onodera, S.; Yoshioka, A.; Matsumoto, N.; Takahara, T.; Nose, Y.; Hirao, M.; Seki, K.; Nishimura, K.; Baik, W.; Hara, H.; Murakawa, T. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: We already clarified that heart rate of young and old persons significantly decreased during standing in water, and that the decreases of heart rate depended on the water depth (Onodera S. 2001, 2006). We speculated that the changes in heart rate could agree with same water depth, not only increase of water depth but also decrease of water depth. Purpose: The purpose of this study was to clarify the relationship between the heart rate and the water depth during increase and decrease of water depth. METHODS: Seven volunteers participated in this study (Age: 23 yrs old).All subjects had an informed consent. A posture was standing in a test tank. It was nine conditions of water depth (on land, knee joint, greater trochanter, xiphoid process, under the collarbone, xiphoid process, greater trochanter, knee joint, on land). Each condition of water depth was kept for a minute. Heart rate was always measured using waterproof electrocardiograph. Water temperature was thirty-four degrees Celsius. Room temperature was twenty-eight degrees Celsius. RESULTS: Heart rate was significantly decreased during increase of water depth (on land: 80 (SD: 9) bpm, knee joint: 73 (SD: 7) bpm, greater trochanter: 70 (SD: 7) bpm, xiphoid process: 63 (SD: 7) bpm, under the collarbone: 62 (SD: 9) bpm). On the other hand, heart rate was significantly increased during decrease of water depth (xiphoid process: 62 (SD: 4) bpm, greater trochanter: 64 (SD: 9) bpm, knee joint: 68 (SD: 5) bpm, on land: 77 (SD: 8) bpm). The changes in heart rate were like a U-curve and were statistically difference (ANOVA, P<0.05). DISCUSSION: It was considered that the main factor of decrease of heart rate was the increase of stroke volume and venous return induced by water pressure. The increase of venous return could be interpreted in imported cell sap from cell to blood. However, as the heart rate did not agree with the same water depth, it could be another functional mechanism of the human body. It could estimate that the autonomic nervous system participated in this phenomenon.